The prostate tissue‐based telomere biomarker as a prognostic tool for metastasis and death from prostate cancer after prostatectomy. (14th July 2022) - Heaphy, Christopher M; Joshu, Corinne E; Barber, John R; Davis, Christine; Lu, Jiayun; Zarinshenas, Reza; Giovannucci, Edward; Mucci, Lorelei A; Stampfer, Meir J; Han, Misop; De Marzo, Angelo M; Lotan, Tamara L; et al.
Abstract: Current biomarkers are inadequate prognostic predictors in localized prostate cancer making treatment decision‐making challenging. Previously, we observed that the combination of more variable telomere length among prostate cancer cells and shorter telomere length in prostate cancer‐associated stromal cells – the telomere biomarker – is strongly associated with progression to metastasis and prostate cancer death after prostatectomy independent of currently used pathologic indicators. Here, we optimized our method allowing for semi‐automated telomere length determination in single cells in fixed tissue, and tested the telomere biomarker in five cohort studies of men surgically treated for clinically localized disease ( N = 2, 255). We estimated the relative risk (RR) of progression to metastasis ( N = 311) and prostate cancer death ( N = 85) using models appropriate to each study's design adjusting for age, prostatectomy stage, and tumor grade, which then we meta‐analyzed using inverse variance weights. Compared with men who had less variable telomere length among prostate cancer cells and longer telomere length in prostate cancer‐associated stromal cells, men with the combination of more variable and shorter telomere length had 3.76 times the risk of prostate cancer death (95% confidence interval [CI] 1.37–10.3, p = 0.01) and had 2.23 times the risk of progression to metastasis (95% CI 0.99–5.02, p = 0.05). The telomere biomarker was associated with prostate cancer death in men with intermediate risk disease (grade groups 2/3: RR = 9.18, 95% CI 1.14–74.0, p = 0.037) and with PTEN protein intact tumors (RR = 6.74, 95% CI 1.46–37.6, p = 0.015). In summary, the telomere biomarker is robust and associated with poor outcome independent of current pathologic indicators in surgically treated men.